Chapter Et in Inferno ego! Sulle narrazioni di anabasi e catabasi d'ispirazione dantesca nelle opere dei romantici polacchi - DE CARLO, Andrea Fernando (Biblioteca di Studi di Filologia Moderna, 2022)
This paper focuses on the anabasis and katabasis narratives inspired by Dante in the works of the most representative Polish romantics: Adam Mickiewicz (1798-1855), Juliusz Słowacki (1809-1849), Zygmunt Krasiński (1812-1859) and Cyprian Kamil Norwid (1821-1883). It was the Divina Commedia which exercised the greatest influence on the poets, especially Inferno, which became a forerunner of the Polish reality itself. But whereas Dante's Inferno is identified with the underworld, the Polish Romantics' locus horridus coincides with the actual world. If the Dantesque journey is a katabasis to the underworld, the descent portrayed by Polish poets is an anabasis towards a volcano crater covered with lava and ice. Moreover, according to the martyrological view, the Polish reality in those days was not only a place of suffering and tribulation, but also of expiation, which was a preparation for the arrival of paradise on Earth.